Dual Effect of Bleomycin on Histopathological Features of Lungs and Mediastinal Fat-Associated Lymphoid Clusters in an Autoimmune Disease Mouse Model - Elewa, Yaser Hosny Ali; Ichii, Osamu; Nakamura, Teppei; Kon, Yasuhiro (Frontiers in Immunology, 2021)
Mediastinal fat-associated lymphoid clusters (MFALCs) are novel immune clusters that function in the pathogenesis of bleomycin (BLM)-induced pneumonitis in a C57BL/6 mouse model. However, we lack literature on the effects of BLM in an autoimmune disease mouse model (AIDM). In the present study, BLM sulfate (BLM group) or phosphate-buffered saline (PBS group) were intranasally administered in BXSB/MpJ-Yaa (Yaa) AIDM and its wild-type strains (BXSB/MpJ “BXSB”) and the histopathology of MFALCs and lungs were examined on days 7 and 21 days. Immunohistochemical analysis was performed to detect lymphatic vessels (LVs), high endothelial venules (HEVs), proliferating, and immune cells. Furthermore, the mRNA expression of Yaa locus genes (TLR7, TLR8, Arhgap6, Msl3, and Tceanc) was detected in the lung tissues. Here, we show a dual effect of BLM on intra-thoracic immune hemostasis among Yaa AIDM and its corresponding wild-type strain (BXSB mice). The BLM group of BXSB mice displayed significantly higher values of lung injury scores (LIS) and size of MFALCs as compared with the corresponding PBS group. However, an opposite effect was detected in Yaa mice. Furthermore, Yaa mice displayed decreased serum autoantibody titers and downregulated expression of TLR7, TLR8, Msl3, and Tceanc in the lungs following BLM administration, especially on day 21. Interestingly, significant positive correlations were detected in both strains between the LIS and the size of MFALCs, LVs, HEVs, and proliferating cells. Conclusively, our findings revealed a crucial function of HEVs on the extent of lung injury and the development of MFALCs in BLM-administered Yaa AIDM and control BXSB mice with dual effects. Moreover, our data suggest that down regulation of Yaa locus genes could contribute as an important attributing factor leading to decrease in the degree of autoimmunity and lung injury in AIDM. Therefore, we suggest that genetic background contributes to BLM diversity among AIDM and the wild-type strain. Targeting some genes or venules could provide novel therapeutic approaches for some autoimmune-associated respiratory diseases via controlling the MFALCs development.